2019
DOI: 10.3389/fnhum.2019.00206
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Correlate Difference Between Positive and Negative Awe

Abstract: Awe is an emotional response to perceptually vast stimuli that transcend current frames of reference. Narrative and experimental work has characterized two distinct variants of awe: positive and negative; however, little is known about the structural neural basis associated with the differences of these two variants of awe. In this study, we investigated the structural neural basis of positive and negative awe underlying individual differences among 62 young healthy adults. Specifically, we assessed the associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 56 publications
(114 reference statements)
0
17
0
Order By: Relevance
“…Although awe is experienced primarily as a positive emotion, there can also be potential negative feelings associated with awe, such as fear, terror, and horror (Arcangeli et al, 2020;Bethelmy, & Corraliza, 2019;Chirico & Yaden, 2018;Guan et al, 2019). This paper, however, examines the positive aspects and benefits of awe.…”
Section: Awe Explainedmentioning
confidence: 97%
“…Although awe is experienced primarily as a positive emotion, there can also be potential negative feelings associated with awe, such as fear, terror, and horror (Arcangeli et al, 2020;Bethelmy, & Corraliza, 2019;Chirico & Yaden, 2018;Guan et al, 2019). This paper, however, examines the positive aspects and benefits of awe.…”
Section: Awe Explainedmentioning
confidence: 97%
“…For example, expert chess players have reduced GMV in the caudate nucleus, precuneus, and occipitotemporal junction (Duan et al, 2012;Hänggi et al, 2014), which are involved in the perception of chess piece positions and quick move generation (Wan et al, 2011). Further, the trait of social emotions, including empathy and awe, are associated with reduced GMV in several brain regions (Banissy et al, 2012;Guan et al, 2019). Notably, we observed that trait respect and empathic concern were associated with reduced GMV in the left ATL.…”
Section: Discussionmentioning
confidence: 62%
“…These results suggest that experiencing ifu is involved in performance improvement. A variety of research on awe suggests that stimuli that are outside of one's viewpoint or experience arouse awe, which motivates one seek new information and update their views or knowledge [29][30][31][32][33][34][35][36][37][38]. Hence, participants who experienced ifu toward the lecturer in the video clip were likely to practice the tips explained by the lecturer and were motivated to improve their scores in the second exam.…”
Section: Discussionmentioning
confidence: 99%